Analisa Antimagic Total Covering Super pada Eksponensial Graf Khusus dan Aplikasinya dalam Mengembangkan Chipertext - Hani'ah Zakin; Ika Hesti Agustin; Kusbudiono Kusbudiono; Dafik Dafik (jcgant, 2021)
Let H_i be a finite collection of simple, nontrivial and undirected graphs and let each H_i have a fixed vertex v_j called a terminal. The amalgamation H_i as v_j as a terminal is formed by taking all the H_i's and identifying their terminal. When H_i are all isomorphic graphs, for any positif integer n, we denote such amalgamation by G=Amal(H,v,n), where n denotes the number of copies of H. The graph G is said to be an (a, d)-H-antimagic total graph if there exist a bijective function f: V(G) E(G) → {1, 2,… ,|V (G)| + |E(G)|} such that for all subgraphs isomorphic to H, the total H-weights w(H)= _vV(H)f(v)+_eE(H)f(e) form an arithmetic sequence {a, a + d, a +2d,...,a+(t - 1)d}, where a and d are positive integers and t is the number of all subgraphs isomorphic to H. An (a,d)-H-antimagic total labeling f is called super if the smallest labels appear in the vertices. In this paper, we study a super (a, d)-H antimagic total labeling of G=Amal(H,v,n) and its disjoint union when H is a complete graph.